Perceived Barriers, Facilitators and Benefits for Regular Physical Activity and Exercise in Patients with Rheumatoid Arthritis: A Review of the Literature - Veldhuijzen van Zanten, J.; Rouse, P.; Hale, E.; Ntoumanis, Nikos; Metsios, G.; Duda, J.; Kitas, G. (Springer International Publishing, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease, which not only affects the joints but can also impact on general well-being and risk for cardiovascular disease. Regular physical activity and exercise in patients with RA have numerous health benefits. Nevertheless, the majority of patients with RA are physically inactive. This indicates that people with RA might experience additional or more severe barriers to physical activity or exercise than the general population. This narrative review provides an overview of perceived barriers, benefits and facilitators of physical activity and exercise in RA. Databases were searched for articles published until September 2014 using the terms ‘rheumatoid arthritis’, ‘physical activity’, ‘exercise’, ‘barriers’, ‘facilitators’, ‘benefits’, ‘motivation’, ‘motivators’ and ‘enablers’. Similarities were found between disease-specific barriers and benefits of physical activity and exercise, e.g. pain and fatigue are frequently mentioned as barriers, but reductions in pain and fatigue are perceived benefits of physical activity and exercise. Even though exercise does not influence the existence of barriers, physically active patients appear to be more capable of overcoming them. Therefore, exercise programmes should enhance self-efficacy for exercise in order to achieve long-term physical activity and exercise behaviour. Encouragement from health professionals and friends/family are facilitators for physical activity and exercise. There is a need for interventions that support RA patients in overcoming barriers to physical activity and exercise and help sustain this important health behaviour.